ENGLISH IS FUN: PENGAJARAN KOSAKATA BAHASA INGGRIS UNTUK MENINGKATKAN ORAL COMMUNICATION SKILL SISWA SEKOLAH MINGGU BUDDHA (SMB) - SAPUTRI, VIKE APRILIANIN MARWINTARIA; SENERU, WISTINA; PRAMUDITA, METTA RICA; RIMAWATI, RIMAWATI (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service is a mentoring activity that seeks to implement English language teaching for Buddhist Sunday School students in groups between lecturers and students. The purpose of this activity is to increase understanding of vocabulary in English with the use of the English is Fun program. The methods used in the English is Fun program include lectures, songs, games, and demonstrations. The results of this community service show that this English is Fun program has succeeded in increasing the interest and confidence of Buddhist Sunday School students to understand the basic material presented and practice English. This can be seen in the enthusiasm and determination of the students to complete all learning activities from start to finish. All those involved at Metta Jaya Monastery were supportive of this community service activity. Based on the results of this program, it can be concluded that the application of English learning teaching in the context of English is Fun is a means of improving the ability of Buddhist Sunday School students to understand English vocabulary effectively. ABSTRAKPengabdian kepada masyarakat merupakan kegiatan pendampingan yang berupaya melaksanakan pengajaran bahasa Inggris kepada para siswa Sekolah Minggu Buddha secara berkelompok antara dosen dan mahasiswa. Tujuan kegiatan ini adalah meningkatkan pemahaman tentang kosakata dalam bahasa Inggris dengan penggunaan program English is Fun. Metode yang digunakan di program English is Fun, antara lain ceramah, lagu dan permainan dan demonstrasi. Hasil dari pengabdian kepada masyarakat ini menunjukkan bahwa program English is Fun ini telah berhasil meningkatkan minat dan kepercayaan diri para siswa Sekolah Minggu Buddha untuk memahami materi dasar yang disajikan dan praktik bahasa Inggris. Hal ini terlihat dari semangat dan tekad para siswa untuk menyelesaikan semua kegiatan pembelajaran dari awal hingga akhir. Semua yang terlibat di Vihara Metta Jaya mendukung terhadap kegiatan pengabdian kepada masyarakat ini. Berdasarkan hasil program ini, dapat ditarik kesimpulan bahwa penerapan pengajaran belajar bahasa Inggris dalam konteks English is Fun menjadi sarana peningkatan kemampuan para siswa Sekolah Minggu Buddha dalam memahami kosakata dalam bahasa Inggris secara efektif.